Prototype Sistem Kontrol Otomatis dan Monitoring Mina Padi Pada Hidroponik Berbasis IOT - Indah Sri Wahyuni (Jurnal Riset Multidisiplin Edukasi, 2025)
Mina-padi farming is a cultivation technique that combines rice and fish cultivation in rice fields to maximize optimal land use. In rice farming, the land required is very large. In this research, a hydroponic system was used to overcome space limitations in rice fields. The designed hydroponic rice field is a system equipped with hardware consisting of an ultrasonic sensor, pH sensor, keypad, RTC, LCD, relay, water pump, and ESP32. The pH sensor shows good consistency and accuracy, but there is a pH error value of 4.18%. The water level control system operates as expected. The software successfully monitors the pH value and water level via ThingSpeak with smooth communication via Wi-Fi. The application of IoT to hydroponic rice fields has proven to be efficient in monitoring and controlling these parameters.